Benin: Do unto your fish... - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Forty years ago, fishers of the coastal lagoons of Benin still used to follow rules handed down from the time of their ancestors. They were usually expressed as religious taboos: do not catch fish when they are too young, do not fish on certain...